Ischemic stroke from basic mechanisms to new drug development - Hsu, Chung Y. (Monographs in clinical neuroscience, 1998)
Stroke is the third leading cause of death in industrialized countries and the number one cause of disability in adults. Ischemic strokes constitute approximately 80% of all strokes, and until recently, no effective therapies had been available. The successful tissue plasminogen activator (tPA) trials open a new era of stroke management with a proven therapeutic now available to patients if they arrive at the hospital within hours of the onset of symptoms. Recent advances in our understanding of the molecular mechanisms of ischemic brain injury and vascular pathology have opened up new avenues for the development of novel therapeutic strategies. The premise that substantial reduction of brain damage after ischemic stroke by therapeutic intervention has now been confirmed in animal stroke models, sets a realistic goal for future treatment of stroke patients. This book covers topics ranging from fundamental molecular mechanisms of ischemic brain injury to the most current views on the clinical stroke trials and academic and industrial efforts to develop new drugs.The authors are leading authorities in their own fields in basic and clinical stroke research. As a timely and comprehensive volume, it will be of immense value to basic and clinical investigators, neurologists and neurosurgeons who manage stroke patients, neuroscientists interested in various aspects of brain injury, and researchers in the pharmaceutical industry who are engaged in new drug development